PROSES PEMBUATAN YOGURT DENGAN MENGGUNAKAN BAKTERI HIDUP PADA BIOKUL VARIAN PLAIN - Ananda Ferga, Sherly; Rahmadani, Fitria; Dias Pertiwi, Eka (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
Yogurt is a fermented milk product that is popular around the world for its distinctive flavor and health benefits. The manufacturing process involves the fermentation of milk with lactic acid bacteria, such as Lactobacillus bulgaricus and Streptococcus thermophilus. This fermentation results in a texture where the right fermentation process is essential to produce quality yogurt, by ensuring optimal bacterial growth and desired flavor characteristics. Once fermentation is complete, the yogurt is refrigerated to stop bacterial activity and prevent further changes in texture and flavor which is thick and sour in taste. Yogurt contains essential nutrients such as protein, calcium, B vitamins, and probiotics, which contribute to digestive and immune system health. Regular consumption of yogurt has been linked to benefits such as improved digestion, reduced risk of heart disease, and improved bone health. As an easily digestible and versatile product, yogurt remains a popular choice for health-conscious consumers.